Effects of Nitrogen and Phosphorus Fertilization and Seeding Patterns on Chemical Composition of Lucerne and Smooth Brome Grass Intercropping System - Yolcu, Halil; Serin, Yunus (Asian Journal of Chemistry, 2010)
Intercropping has been used widely in forage plant production all around the world. In intercropping systems, forage plants need different requirements are grown together. Requirement of fertilization and seeding pattern of intercropping differ from mono cropping. The research goals were to evaluate the effects of various seeding patterns and fertilization on the crude protein and chemical content of lucerne-smooth brome grass mixture under field conditions in 2002-2003. Lucerne and smooth bromegrass mixtures were established with different seeding patterns (mixed, alternative and cross-seeding), N fertilizer rates (0, 60 and 120 kg N ha-1) and P fertilizer rates (0, 40, 80 and 120 P2O5 ha-1). The results of this study indicated that different seeding patterns, N and P fertilization affected chemical contents of alfalfa and smooth brome grass mixture in the intercropping system. Depending on different seeding patterns, N, Ca, K and Mg content varied significantly, but no P content in the intercropping system. Nitrogen application increased N content and P application likewise increased P content. While P application increased N content, N application had no effect on the P content of the intercropping. Calcium and K did not vary significantly depending on N and P fertilization; yet, a relationship between P application and Mg content was determined.